Pigs lacking the SRCR5 domain of CD163 protein demonstrate heritable resistance to the PRRS virus and no changes in animal performance from birth to maturity - Nesbitt, Clint; Galina Pantoja, Lucina; Beaton, Benjamin; Chen, Ching-Yi; Culbertson, Matt; Harms, Perry; Holl, Justin; Sosnicki, Andrzej; Reddy, Srinu; Rotolo, Marisa; Rice, Elena (Frontiers in Genome Editing, 2024)
Porcine Reproductive and Respiratory Syndrome (PRRS) is one of the most persistent globally viral pig diseases with a significant economic impact on the pig industry. PRRS affects pigs of all ages causing late-term abortions and stillbirths in sows, as well as respiratory disease in piglets and increased susceptibility to secondary bacterial infection with a high mortality rate. PRRS disease is caused by a positive single-stranded RNA PRRS virus (PRRSV), which has a narrow host cell tropism limited to monocyte-macrophage lineage cells. Several studies demonstrated that the removal of CD163 protein or, as a minimum, its scavenger receptor cysteine-rich domain 5 (SRCR5) precludes viral genome release, conferring resistance to PRRSV in live animals. Today, very limited information exists about the impact of such edits on animal performance from birth through maturity in pigs. Using CRISPR-Cas9 with dual guide RNAs and non-homologous end joining, first generation (E0) pigs were produced with a deletion of exon 7 in the CD163 gene. Selected pigs were bred to produce the next three generations of pigs to establish multiple lines of pigs homozygous for the edited allele and confirmed that the CD163 gene with removed exon 7 was stable through multiple breeding cycles. The pigs were evaluated relative to non-edited pigs from birth to maturity, including any potential changes in meat composition and resistance to PRRSV. This study demonstrates that removing the SRCR5 domain from the CD163 protein confers resistance to PRRSV and, relative to unedited pigs, resulted in no detected differences in meat composition and no changes in growth rate, health, and ability to farrow. Together, these results support the targeted use of gene editing in livestock animals to address significant diseases without adversely impacting the health and well-being of the animals or the food products derived from them.